MODELING SIZE-DENSITY RELATIONSHIP AND THINNING REGIME FOR THE MANAGEMENT OF TECTONA GRANDIS STANDS IN ADO TEAK PLANTATION, EKITI STATE, NIGERIA - Clement, Segun A. (FUDMA JOURNAL OF SCIENCES, 2022)
Tectona grandis is used for sawn timber, poles, cutting boards, indoor flooring, as a veneer for indoor finishing, medicinal products and shade in Ijan community. Therefore, it is necessary to determine the limits of the possible maximum density the stands can sustain that would lead actions to control competition and growing space. A total of thirty (30) temporary sample plots of 400 m2 in an even-aged stands of the plantation was laid. Density, quadratic mean diameter, height diameter and volume models were processed and estimated. The results showed that model one (1) of the H-D, model three of the volume and the stochastic frontier half normal (SF HN) model had the lowest selection indices, therefore, were selected as the grand and suitable models for proper management of the plantation. The stochastic frontier half normal (SF HN) model was apt to raise Reineke’s model parameters and applied to predict the stand density index. The stand density index allowed the simulation of thinning regime for the stand and suggested the best management strategies to optimize the growing space and the redistribution of growth of the remaining trees. These tools are keys for decision making when proposing cutting intensities in thinnings that prepare the plantation for the final harvest. The thinning regime should be specific for each stand, depending on its quadratic mean diameter and the number of trees per hectare, as well as the type of products to which the trees are to be removed.